Institutionalizing local government accountability: a case of Nabire, Indonesia - Suripatty, Petrus Izaach; Edyanto, Edyanto (Department of Government Studies, Universitas Muhammadiyah Makassar, 2023)
This research investigates the challenges and opportunities associated with institutionalizing local government accountability, with a focus on the case of Nabire. The central research problem addressed is the intricate interplay between legislative-institutional relations and executive accountability, focusing on a specific case study that delves into the performance and transparency of the Regent of Nabire. The methodology involves a comprehensive examination of the Regent's actions and decisions, scrutinizing their adherence to legal frameworks, responsiveness to public concerns, and collaboration with the legislative body. Results indicate that while Nabire has made significant strides in certain areas of local government accountability, challenges persist, including issues related to resource allocation, capacity building, and community engagement. The study recommends tailored strategies for enhancing local government capacity, promoting community participation, and fostering collaboration between different levels of governance to ensure effective institutionalizing in Nabire. The findings contribute valuable insights to the broader discourse on improving local governance models, particularly in regions facing similar socio-economic and environmental challenges.